(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Introduction: The tuberculosis prevalence survey was carried out in Nepal in 2019 provided a new estimation for Tuberculosis with a prevalence of 117,000, incidence of 69,000, death of 17,000, and Drug Resistance Tuberculosis (DRTB) of 2,200 which is a prevalence of 1.8 times, the incidence of 1.6 times, mortality of 3.1 times, and DRTB is 1.57 times higher than the previous estimation in Nepal. The Government of Nepal has made several commitments in the national and international forums to eliminate TB from the country by 2035. The objective of the review was to gather and compile thecommitments of Nepal to ending Tuberculosis in the country. Methodology: Published articles, grey reports, and progress reports of the Nepal National Tuberculosis Program related information collected from the Google search engine using keywords such as national commitment to end TB. All relevant manuscripts and reports were reviewed using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. Documents were analysed and the main messages were summarized in terms of their relevance to the Ending TB strategy. Results: The Government of Nepal has made several commitments in international forums to eliminating Tuberculosis, some of which are the WHO-Global Ministerial Conference on Ending TB in Sustainable Development Era in Moscow, United Nations General Assembly High-Level Meeting (UNHLM) on TB, and Delhi End TB Summit. In the year 2018, the elected parliamentarians also pledged to extend their full commitment toward ending TB and HIV in Nepal. Furthermore, in the recent past, the Prime ministers of Nepal have formally expressed their commitment to adopt a multisectoral collaborative framework and implement TB-free initiatives in the country during their tenures. Nepal also participated and reinforced the commitments in the ministerial-level meeting to renew the TB response in the South East Asia Region in 2021. Conclusion: All pledges are instrumental to increase multisectoral collaboration, domestic funding, and effective leadership in the TB programme. Effective implementation of the TB-free initiative nationwide is critical for attaining SDG and END TB targets by 2035.